2022
DOI: 10.1186/s12891-021-04965-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the size of the trunk inclination angle in the early detection of scoliosis in children

Abstract: Background Early detection of idiopathic scoliosis is one factor in determining treatment effectiveness. Therefore, the aim of this study was to assess the importance of the size of the trunk inclination angle (ATI) for the early detection of scoliosis in preschool- and school-age children, taking into account the location and size of the spine curvature. Methods The study included a group of 216 children (mean age 11.54 years, standard deviation ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…When analysing the differences in the morphology of scoliosis curvatures in relation to the location in the study, it should be emphasized that low-rotated curvatures were significantly more frequent in the lumbar and thoracolumbar sections, which is consistent with the data in the literature [ 2 , 10 , 24 ]. Scoliosis of the first degree (10°-24° Cobb) located in the lumbar region, which develops in the type of low-rotated curvature, may be clinically manifested only by asymmetry of the waist angles, with slight ATI, while an X-ray often shows a significant Cobba ≥ 10 ° angle.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…When analysing the differences in the morphology of scoliosis curvatures in relation to the location in the study, it should be emphasized that low-rotated curvatures were significantly more frequent in the lumbar and thoracolumbar sections, which is consistent with the data in the literature [ 2 , 10 , 24 ]. Scoliosis of the first degree (10°-24° Cobb) located in the lumbar region, which develops in the type of low-rotated curvature, may be clinically manifested only by asymmetry of the waist angles, with slight ATI, while an X-ray often shows a significant Cobba ≥ 10 ° angle.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, other authors found that the ATI/Cobb correlation in 6–9 year old children with scoliosis in the lumbar region is not high [ 4 , 8 , 9 ]. It should be emphasized that the abovementioned morphological types of curvature may be characteristic of all curvatures of scoliosis [ 24 , 29 ] or, what happens much more often, different types refer to its fragment, e.g., low rotation in the lumbar spine and medium or vice versa in the thoracic spine [ 5 , 24 ]. Moreover, with growth and/or progression, the type of low-rotated curvature can change into medium or even high-rotated curvature [ 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations